Utilizing Calibration Model for Water Distribution Network Leakage Detection - Geumchae Shin; Soon Ho Kwon; Suhyun Lim; Seungyub Lee (Engineering Proceedings)
Leakage presents a significant challenge in water distribution network (WDN) planning and management. This study introduces a novel methodology for hydraulic model calibration and leak detection based on MCMC-Statistical Distance. The central hypothesis posits that the presence of leaks induces fluctuations in estimated pipe roughness coefficients (PRCs) as the pipe flow changes, reflecting the altered behavior of leaking pipes in energy dissipation. The proposed model comprises two distinct algorithms: (1) PRC estimation using MCMC and (2) a leakage detection algorithm employing a Kolmogorov–Smirnov test. Demonstrated in a simple water distribution network with various scenarios, the results illustrate the model’s potential for real-time leak detection.